Influence of social determinants on oral health in indigenous populations of the Americas. Literature review - Isidro-Olán, Laura Beatriz (2022)
Indigenous populations frequently have their oral and general health affected due to cultural conditions, social marginalization, and geographic separation from urbanized areas. The degree of health achieved by a population is the result of multiple environmental, social, behavioral, genetic and health service determinants. The determinants depend, in turn, on economic and social policies and, above all, on the organized social response to health and disease phenomena. Health determinants such as: educational level, economic income, accessibility to health services, have a negative or positive influence on population health status. Likewise, characteristics such as the distribution of health professionals in the territory, cultural conditions such as linguistic, cultural and worldview barriers of indigenous peoples, hinder the health care received by this population group considered as vulnerable. It is concluded that the influence of health determinants on oral health in indigenous populations should be considered for inclusion in the design of preventive dental models, according to their reality. Cultural differences in terms of language and communication, values, beliefs, ways of life, organization of time, as well as considerations of the social determinants of health and health behaviors, contribute significantly to oral health conditions and to the design of primary health care models or preventive models for vulnerable population groups, thus contributing to the inclusion and promotion of health.